2003
DOI: 10.1002/chin.200343005
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Reactions of Hg with Halogens: Atmospheric Implications.

Abstract: Theory Theory C 1000 A Theoretical Study on the Reactions of Hg with Halogens: Atmospheric Implications. -(KHALIZOV*, A. F.; VISWANATHAN, B.; LARREGARAY, P.; ARIYA, P. A.; J. Phys. Chem. A 107 (2003) 33, 6360-6365; Dep. Chem., McGill Univ., Montreal, Que. H3A 2K6, Can.; Eng.) -Schramke 43-005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Previous laboratory studies reported apparent rate coefficients in the range of (3.6 ± 0.9) × 10 −13 to (3.2 ± 0.3) × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [19,20,22]. Theoretical studies estimated the rate constants to be from 9.8 × 10 −13 to 2.1 × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [3,21,23]. Theoretical and experimental rate constants for mercury oxidation by Br and Cl atoms at 298 K have previously been compared in detail in Table A.2 by Subir et al [18].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous laboratory studies reported apparent rate coefficients in the range of (3.6 ± 0.9) × 10 −13 to (3.2 ± 0.3) × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [19,20,22]. Theoretical studies estimated the rate constants to be from 9.8 × 10 −13 to 2.1 × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [3,21,23]. Theoretical and experimental rate constants for mercury oxidation by Br and Cl atoms at 298 K have previously been compared in detail in Table A.2 by Subir et al [18].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 96%
“…Here we discuss recent advances in the understanding of the oxidation of Hg 0 by halogen atoms and NO3 radicals, as well as determining the major oxidant(s) in the atmosphere. Adapted and modified from [3]. The question mark (?)…”
Section: Chemical Redox Pathways In the Gas Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Other theoretical [Khalizov et al, 2003;Goodsite et al, 2004] and experimental [Ariya et al, 2002] estimates of k 1 are faster (see Table 1), although Donohoue et al [2006] argue that these values are less accurate. The fastest k 1 value with reported temperature dependence [Khalizov et al, 2003] implies t global = 160 days, after recalculating k 2 to keep the k 1 :k 2 balance [Goodsite et al, 2004].…”
mentioning
confidence: 99%